Hemitaeniochromis brachyrhynchus, a new species of cichlid fish from Lake Malaŵi, with comments on some other supposed members of the genus (Teleostei: Cichlidae) - Oliver, Michael K. (Zootaxa, 2012)
Hemitaeniochromis brachyrhynchus, an anatomically distinctive and apparently rare new cichlid, is described and illus-trated from specimens collected at two widely separated localities within Lake Malaŵi. It is easily distinguished from H.urotaenia, type species of the genus, by its narrow lacrimal bone which is only one-third of the orbit length, a characterthought to be unique not only in Hemitaeniochromis but among all known Lake Malaŵi cichlids. The genus Hemitaenio-chromis Eccles & Trewavas (1989) is redefined to allow provisional inclusion of this new species. Two species placed inProtomelas by Eccles & Trewavas (1989) [P. insignis (Trewavas) and P. spilopterus (Trewavas)] were recently transferredto Hemitaeniochromis by some authors, without much evidence. The generic placement of these controversial taxa, and of several undescribed species known only from underwater photographs, is briefly reconsidered.